Establishment and comparison of different procedures for modeling intrauterine adhesion in rats: A preliminary study - Peng-Cheng Liu; Yu-Ting Song; Long-Mei Zhao; Yan-Ling Jiang; Jun-Gen Hu; Li Dong; Xing-li Zhou; Li Zhou; Yaxing Li; Jesse Li-Ling; Hui-Qi Xie (Heliyon, 2024)
The establishment of a stable animal model for intrauterine adhesion (IUA) can significantly enhance research on the pathogenesis and pathological changes of this disease, as well as on the development of innovative therapeutic approaches. In this study, three different modeling methods, including phenol mucilage combined mechanical scraping, ethanol combined mechanical scraping and ethanol modeling alone were designed. The morphological characteristics of the models were evaluated. The underlying mechanisms and fertility capacity of the ethanol modeling group were analyzed and compared to those of the sham surgery group. All three methods resulted in severe intrauterine adhesions, with ethanol being identified as a reliable modeling agent and was subsequently subjected to further evaluation. Immunohistochemistry and RT-PCR results indicated that the ethanol modeling group exhibited an increase in the degree of fibrosis and inflammation, as well as a significant reduction in endometrial thickness, gland number, vascularization, and endometrial receptivity, ultimately resulting in the loss of fertility capacity. The aforementioned findings indicate that the intrauterine perfusion of 95 % ethanol is efficacious in inducing the development of intrauterine adhesions in rats. Given its cost-effectiveness, efficacy, and stability in IUA formation, the use of 95 % ethanol intrauterine perfusion may serve as a novel platform for evaluating innovative anti-adhesion materials and bioengineered therapies.